Anthelmintic efficacy of Clerodendrum viscosum on fowl tapeworm Raillietina tetragona - Suranjana Nandi; Bidisha Ukil; Saptarshi Roy; Suman Kundu; Larisha Mawkhlieng Lyndem (Taylor & Francis Group, 2017)
Context: Clerodendrum viscosum Vent. (Verbenaceae) is a shrub, widely used amongst the natives of India against various diseases. Objective: Crude extract of the plant was tested in vitro on a tapeworm Raillietina tetragona Molin (Davaineidae) to evaluate its potential anthelmintic efficacy and ultrastructural changes in the parasite. Materials and methods: Parasites were exposed to different concentrations of ethanolic leaf extract (10-80 mg/mL) and praziquantel (0.0005-0.005 mg/mL) and incubated in phosphate-buffered saline (PBS). The pH was 7.4 at 37 °C, while one set of worms was incubated only with PBS as a control. Permanent immobilization of worms was determined visually when no motility occurred on physically disturbing them. The parasites exposed to high concentrations of leaf extract and praziquantel treatments were processed for histological and electron microscopic studies, as these concentrations took the least time for paralysis and death to occur. Result: With an increase in the concentration of the leaf extract from 10 to 80 mg/mL and praziquantel from 0.0005 to 0.005 mg/mL, the time for the onset of paralysis and death was shortened. The treated parasites lost their spontaneous movement rapidly followed by death. Electron microscopic observations revealed disruptions in the tegument and parenchymal layer, accompanied by deformities in cell organelles. Discussion and conclusion: Extensive structural alterations in the tegument indicate that the plant-derived components cause permeability changes in the parasite leading to paralysis and subsequent death. These observations suggest that phytochemicals present in C. viscosum have vermifugal or vermicidal activity, and thus may be exploited as alternative chemotherapeutic agents.